EXPLORING QUALITY DETERMINANTS IN AIRLINE SERVICES: A STUDY OF CUSTOMER EXPERIENCE IN VIETNAM - Y Nha Ngoc Hoang; Vikas Kumar; Marlene Amorim (International Journal of Organizational Business Excellence, 2019)
The increasing prices of oil, rank as one of the main threats to airlines. Generally, all airlines will adjust their prices to deal with oil price variations, and this often impacts customer service satisfaction. However, there tends to be gapin research exploring the relationship between the changing oil prices and its impact on customer satisfaction in the airline sector. This research gap widens particularly in the context of an airline operating in the developing country context. This study therefore explores the relationship between oil prices, perceived service quality, customer loyalty and customer satisfaction for a Vietnamese airline. The study reports the findings from a survey of 235 passengers of Vietnam airlines and explores the relationships between prices, service quality, service satisfaction and loyalty. Our findings indicate that increasing oil prices do affect the customer satisfaction negatively however customer loyalty largely remains unaffected.